2D/3D echocardiographic determinants of left ventricular reverse remodelling after MitraClip implantation. (8th November 2018) - Cimino, Sara; Maestrini, Viviana; Cantisani, Donatella; Petronilli, Valentina; Filomena, Domenico; Mancone, Massimo; Sardella, Gennaro; Fedele, Francesco; Lancellotti, Patrizio; Agati, Luciano
Abstract: Aims: The aim of this study was to describe incidence and determinants of left ventricular reverse remodelling (r-LVR) at 6 months follow-up after MitraClip implantation in patients with secondary severe mitral regurgitation (MR) and reduced left ventricular ejection fraction (LVEF). Methods and results: Forty-five patients, undergoing MitralClip implantation with low ejection fraction and high surgical risk were enrolled in this study. Three of them died before the scheduled 6 months follow-up period and one patient had cardiac surgery due to MitraClip detachment. All patients underwent transthoracic 2D and 3D echocardiography before and 6 months after the procedure. A significant MR severity reduction and an improvement in New York Heart Association (NYHA) class were detected in all patients. The study population was divided in two groups according to the presence of r-LVR (51%, n  = 23 patients) or not (non-rLVR group, 18 patients). Non-significant differences in MR aetiology and number of clips implanted were found. Left ventricular reverse remodelling patients showed significant lower values of logistic EuroSCORE and STS score, left ventricular end-diastolic volume index (LVEDV/i), right ventricular end systolic area, and pulmonary artery systolic pressure (PASp) at baseline evaluation. At multivariable analysis, baseline PASp value resulted to be the only independent predictor of r-LVR [odds ratio 95% confidence interval 0.94 (0.89–0.99), P  = 0.021]. In r-LVR patients, a significant improvement in LVEF and global longitudinal strain and a reduction in left atrial volume index were detected after 6 months, whereas in non-rLVR subgroup a significant increase in both LVEDV/i and left ventricular end-systolic volume index was observed at follow-up. Conclusion: Even if a reduction of MR was detected in all patients after MitralClip implant, our findings suggest that end-stage patients presenting with higher left ventricular volumes, logistic scores, and PASp may not benefit from the procedure at longer follow-up in terms of left ventricular function.